2015
DOI: 10.1016/j.visres.2014.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic integration of information about salience and value for smooth pursuit eye movements

Abstract: Eye movement behavior can be determined by bottom-up factors like visual salience and by top-down factors like expected value. These different types of signals have to be combined for the control of eye movements. In this study we investigated how smooth pursuit eye movements integrate salience and value information. Observers were asked to track a random-dot kinematogram containing two coherent motion directions. To manipulate salience, the coherence or the density of one of the motion signals was varied. To … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 65 publications
0
7
0
Order By: Relevance
“…Nonetheless, our results demonstrate overall that aSPEMs are sensitive to the rewarding value of a stimulus even when the reward is related to the nonvisually guided phase of pursuit rather than the visually guided phase (Brielmann & Spering, 2015;Joshua & Lisberger, 2012;Schütz et al, 2015) and that reinforcement contingencies have to be taken into account in addition to attentional factors (Khurana & Kowler, 1987) and prediction (G. R. Barnes, Barnes, & Chakraborti, 2000; G. R. Barnes & Donelan, 1999;Santos & Kowler, 2017;Wells & Barnes, 1998) for the buildup of prior expectation about a target's direction.…”
Section: Direction Bias and Reward Contingenciesmentioning
confidence: 73%
See 1 more Smart Citation
“…Nonetheless, our results demonstrate overall that aSPEMs are sensitive to the rewarding value of a stimulus even when the reward is related to the nonvisually guided phase of pursuit rather than the visually guided phase (Brielmann & Spering, 2015;Joshua & Lisberger, 2012;Schütz et al, 2015) and that reinforcement contingencies have to be taken into account in addition to attentional factors (Khurana & Kowler, 1987) and prediction (G. R. Barnes, Barnes, & Chakraborti, 2000; G. R. Barnes & Donelan, 1999;Santos & Kowler, 2017;Wells & Barnes, 1998) for the buildup of prior expectation about a target's direction.…”
Section: Direction Bias and Reward Contingenciesmentioning
confidence: 73%
“…In newborn infants (1-7 days), Darcheville, Madelain, Buquet, Charlier, and Miossec (1999) found that smooth eye movements can be enhanced using an auditory reinforcer contingent to the eye velocity. Schütz, Lossin, and Gegenfurtner (2015) showed that, in presence of two moving textures, pursuit direction choice is mainly determined by the target's visual salience at initiation, but 300-400 ms after motion onset, pursuit steered toward the rewarded direction, and the salience effects gradually disappeared. On the other hand, Joshua and Lisberger (2012) reported an influence of precued reward contingencies already on vector average pursuit initiation in monkeys.…”
Section: Introductionmentioning
confidence: 99%
“…Active and preplanned strategies are not mutually exclusive in that actual patterns of sensor movements seem to be influenced by some mixture of them. For example, eye movements have been found to be best predicted by a combination of several bottom-up (such as saliency) and top-down (such as reward) factors [34, 35, 36] where the contribution of these different factors can depend on the timing requirement of the task and the time course and type of eye movement [37, 38, 39, 40, 41].…”
Section: Taxonomy Of Efficient Sensing Strategiesmentioning
confidence: 99%
“…The pursuit system does not depend solely on low level sensory features. For example, the size of the reward can determine the gain of the pursuit ( Joshua and Lisberger, 2012 ; Brielmann and Spering, 2015 ; Schutz et al, 2015 ). Therefore, we expected that objects that were significant to the monkeys before training would potentiate pursuit.…”
Section: Discussionmentioning
confidence: 99%